Implementation of Chatbot-Based Digital Services to Optimize Community Service Processes in Inbate Village, Indonesia – Timor Leste Border Area - Donatus J Manehat; Sisilia D. B Mau; Yovinia Carmeneja Hoar Siki (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Inbate Village is located in the border area between Indonesia and Timor Leste and still experiences limitations in public service accessibility. Administrative services are mostly conducted manually, causing delays, increased workload for village staff, and difficulties for citizens in obtaining information. This community service activity aimed to implement chatbot-based digital services to improve the efficiency, accessibility, and transparency of public services in Inbate Village. The implementation method included needs analysis, chatbot development, training and socialization, implementation, and evaluation stages. The chatbot was integrated into the village website and WhatsApp platform to provide administrative information, document requirements, service schedules, and complaint services. The activity was conducted over eight months, starting from September 2025 until April 2026. The implementation schedule consisted of preparation and needs analysis in September 2025, chatbot development during October–November 2025, training and socialization in December 2025, implementation and monitoring from January to February 2026, and evaluation and refinement during March–April 2026. The results showed that the chatbot successfully improved service effectiveness, reduced queues at the village office, and enhanced digital literacy among village officials and residents. This activity also provides a model for AI-based public service implementation in border areas.